1995
DOI: 10.1074/jbc.270.10.5549
|View full text |Cite
|
Sign up to set email alerts
|

The APC Protein and E-cadherin Form Similar but Independent Complexes with α-Catenin, β-Catenin, and Plakoglobin

Abstract: The tumor suppressor APC protein associates with the cadherin-binding proteins alpha- and beta-catenin. To examine the relationship between cadherin, catenins, and APC, we have tested combinatorial protein-protein interactions in vivo, using a yeast two-hybrid system, and in vitro, using purified proteins. beta-Catenin directly binds to APC at high and low affinity sites. alpha-Catenin cannot directly bind APC but associates with it by binding to beta-catenin. Plakoglobin, also known as gamma-catenin, directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
166
0
4

Year Published

1997
1997
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(174 citation statements)
references
References 38 publications
(19 reference statements)
4
166
0
4
Order By: Relevance
“…Interestingly, the same amino acid substitution has been demonstrated at codon 41 in exon 3 of the β-catenin gene in 2 endometrial carcinoma tissues (Fukuchi et al, 1998). γ-catenin shares strong amino acid similarity with β-catenin, binds APC and Tcf, and exhibits signalling activity similar to that of β-catenin (Karnovsky and Klymkowsky, 1995;Rubinfeld et al, 1995;Sacco et al, 1995). γ-catenin mutation in H1726 cells might be involved in activation of the APC/β-catenin/Tcf signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the same amino acid substitution has been demonstrated at codon 41 in exon 3 of the β-catenin gene in 2 endometrial carcinoma tissues (Fukuchi et al, 1998). γ-catenin shares strong amino acid similarity with β-catenin, binds APC and Tcf, and exhibits signalling activity similar to that of β-catenin (Karnovsky and Klymkowsky, 1995;Rubinfeld et al, 1995;Sacco et al, 1995). γ-catenin mutation in H1726 cells might be involved in activation of the APC/β-catenin/Tcf signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The major aim of this study was to explore the di erences in the interaction of b-catenin and plakoglobin with the ubiquitin-mediated degradation machinery that could be responsible for their di erent turnover and signaling activity. Previous studies have demonstrated that plakoglobin, similar to b-catenin, can interact with the GSK/APC/Axin system that regulates b-catenin stability (Hulsken et al, 1994;Rubinfeld et al, 1995;Kodama et al, 1999). In principle, di erences in the interaction of the two catenins with the ubiquitin-proteasome system could be due to either di erential phosphorylation of the two proteins by the GSK/APC/Axin complex, or to di erent processing by the ubiquitin system.…”
Section: Discussionmentioning
confidence: 99%
“…b-TrCP and its Drosophila homolog Slimb were implicated in the regulation of wnt/wg signaling (Jiang and Struhl, 1998) and the DF-b-TrCP mutant, lacking the F-box, was shown to induce axis duplication in Xenopus (Marikawa and Elinson, 1998;Liu et al, 1999), and loss of function mutations in Slimb, induce the accumulation of armadillo in Drosophila (Jiang and Struhl, 1998). Plakoglobin is also capable of associating with the GSK/APC/Axin complex (Hulsken et al, 1994;Rubinfeld et al, 1995;Kodama et al, 1999), but its degradation by the ubiquitin-proteasome system is less pronounced than that of b-catenin , and its mode of interaction with the b-TrCP ubiquitin ligase was not determined.…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminus contains an oligomerization domain followed by seven repeats of an Armadillo motif. The middle portion of APC contains three successive 15-amino acid (aa) repeats followed by seven related but distinct 20-aa repeats, both of which are able to bind independently to b-catenin (Su et al, 1993;Rubinfeld et al, 1993Rubinfeld et al, , 1995. Following the 20-aa repeats is a basic region, while the C-terminus has a S/ TXV motif that interacts with the PDZ domaincontaining human homolog Dlg (Matsumine et al, 1996).…”
Section: Introductionmentioning
confidence: 99%